Effects of Lactobacillus acidophilus and L. reuteri on bone mass and gut microbiota in ovariectomized mice: Effects of LA and LR on BM and GM in OVX mice - Chen, Jingchen; Liu, Xianyin; Li, Songbo; Li, Jianwen; Fang, Guanjun; Chen, Yaoxin; Zhang, Xiaoqian (Cellular and Molecular Biology, 2023)
Lactobacillus acidophilus is widely used as a food additive or medication in our daily lives. The objective of this study was to investigate the effects of L. acidophilus and L. reuteri on bone mass in OVX mice and their associated mechanisms. Fifty 6-week-old female C57BL/6J mice were subjected to five different treatments: sham surgery, OVX surgery, OVXandL. reuteri fed, OVXandL. acidophilus fed, OVXandboth L. reuteri and L. acidophilus co-fed, respectively. Serum samples were collected, and IL-1β,IL-6,TNF-α, and OCN levels were determined. The bone volume fraction and trabecular number, trabecular thickness, trabecular separation, and cortical thickness of the mice were analyzed by micro-CT in both femurs. Mice feces were taken for Illumina high-throughput sequencing to analyze the microbial composition and characteristics. After probiotic feeding, the bone volume fraction, the trabecular number, and the trabecular thickness increased, and the trabecular separation decreased in OVX mice. IL-1β, IL-6, and TNF-α in the blood significantly decreased. The observed Chao1 and ACE indexes increased significantly. Changes in intestinal microorganisms occurred in all groups of mice. The change of index in the gut microbes, may indicate that the bone mass of OVX mice is changing. L. acidophilus shares the same role as L. reuteri in preventing bone loss in OVX mice. The mechanism of action may be through inhibition of the activation of inflammatory factors in the osteoclast activation pathway in bone metabolism, modulation of gut microbial diversity, and alteration of the richness of specific microorganisms that lead to attenuation of bone loss.